Comparison of baseline and postconcussion SCAT3 scores and symptoms in varsity athletes: an investigation into differences by sex and history of concussion - Hurtubise, Johanna M (BMJ Open Sport Exerc Med, 2018)
OBJECTIVE: To investigate the use of the Sport Concussion Assessment Tool 3 (SCAT3) as an assessment tool in the varsity population, as well as the effects of sex and concussion history on both baseline and postconcussion scores. METHODS: A comparison between baseline and postconcussion SCAT3 scores of varsity level athletes was conducted through retrospective chart review. Differences in both baseline and postconcussion scores were further analysed by sex and history of concussion. RESULTS: The only clinically significant change on the SCAT3 elicited by a concussion was that of self-reported symptoms. There were no clinically significant differences based on sex or history of concussion. CONCLUSION: The SCAT3 in its entirety may not be useful in this population. Additional research on sociocultural and sport aspects that may be affecting symptom reporting in this population is needed.